Anti-Inflammatory Nutrition as a Pharmacological Approach to Treat Obesity - Barry Sears; Camillo Ricordi (Hindawi Limited, 2011)
Obesity is a multifactorial condition resulting from improper balances of hormones and gene expression induced by the diet. Obesity also has a strong inflammatory component that can be driven by diet-induced increases in arachidonic acid. The purpose of this paper is to discuss the molecular targets that can be addressed by anti-inflammatory nutrition. These molecular targets range from reduction of proinflammatory eicosanoids to the modulation of features of the innate immune system, such as toll-like receptors and gene transcription factors. From knowledge of the impact of these dietary nutrients on these various molecular targets, it becomes possible to develop a general outline of an anti-inflammatory diet that can offer a unique synergism with more traditional pharmacological approaches in treating obesity and its associated comorbidities.